Mismatch Repair-Deficient Cancers Are Targets for Anti-PD-1 Therapy - Kelderman, Sander; Schumacher, Ton N; Kvistborg, Pia (Cancer cell, 2015)
Immune checkpoint-blocking therapies have yielded positive clinical data in a series of human malignancies. Recent work from Le and colleagues strongly supports the use of these therapies for mismatch repair-deficient tumors, independent of underlying tumor type. These data suggest the importance of sensing the consequences of DNA damage in cancer immunotherapy.